Weaving webs of compliance: integrating vertical and horizontal prevention of corporate involvement in human rights violations - Huisman, Wim (Corporate crime, 2026)
Corporate involvement in human rights abuses has only recently been introduced as a specific form of corporate crime and added to the criminology of white-collar crime. Yet, corporate involvement in human rights violations is widespread over various branches of industry. The lack of internationally binding law and regulations has given rise to a range of different actors and a multitude of diverse instruments to ensure corporate compliance with human rights and prevent involvement in serious international crimes. In this chapter, we interrogate the possible mechanisms for preventing and controlling corporate involvement in human rights violations from the perspective of situational crime prevention. We start by contrasting the dominant, hierarchical model of the regulatory pyramid with the horizontal approach of situational crime prevention. We then introduce a “web of compliance” connecting different actors across contexts as a critical step in reducing the role of corporations in – directly and indirectly – perpetuating human rights violations.